Proposed Innovative Correlations for some Nuclear and Radiological Fields using Theorem of S. El-Mongy - El-Mongy, Sayed (JOURNAL OF ADVANCES IN PHYSICS, 2021)
Thinking and thought are divine urge in the Great Quran. The published S. El-Mongy theorem (L= eπrsA) correlates eπ with radius r of circular and spherical geometries by a factor sA (θ/10ϕ) to be used for calculations of arc length and astronomical distance. In this article, Sayed’s formula was used to produce correlations with the well-established laws and formulas of different nuclear and radiological fields. The formula was directed to be correlated with half-life time, activity, flux, reaction rate, reactor power, mean free path, photon fluence rate, radiation dose rate and half value thickness equations. It was also oriented to calculate fuel rods circumstances of different reactor types; PWR, BWR, VVER1200 and Candu-6. The produced correlations of eπ and sA with the above mentioned topics are given with simplified reduced forms, limitation and some comparative calculations between old and the proposed innovative formulas. New formulas for sphere volume and surface area and cylinder are also given based on eπ term.